Celiac-Like Duodenopathy Associated With Enteric-Coated Mycophenolate Sodium Immunosuppression in Renal Transplant Recipients: Report of 4 Cases - Ivanovski, Ninoslav; Severova Andreevska, Galina; Ivanovski, Ognen; Petrushevska, Gordana; Nikolov, Igor; Dohcev, Saso; Labacevski, Bojan; Popov, Zivko (My University, 2023)
Celiac-like disease and celiac sprue associated with widespread use of mycophenolic acid are among the most frequent complications of renal transplant. Most cases have been observed in patients receiving mycophenolate mofetil; however, there have been rare instance after administration of enteric-coated mycophenolate sodium. Here, we describe 4 renal transplant recipients with celiac-like duodenopathy that occurred in association with enteric-coated mycophenolate sodium treatment in a time period of 14 to 19 years after living donor kidney transplant. Three of 4 patients had diarrhea, and all 4 patients had marked loss of body weight. Esophago-gastroduodenoscopy was not diagnostically helpful; however, randomly performed duodenal biopsies showed mild villous atrophy and intraepithelial lymphocytosis. Replacement of enteric-coated mycophenolate sodium with azathioprine was successful with stopping diarrhea, allowing regained body weight, and stabilization of renal function. This potential complication in kidney transplant recipients can occur more than a decade after transplant. Diagnosis and treatment initiation are urgent to cure this disease.
Keywords: Celiac-like disease; kidney transplant; long-term complications